Analysis of Adab Education According to Syed Muhammad Naquib Al-Attas - Putra, Purniadi; Mawazi, Mawazi; Hifza, Hifza (Faculty of Education Universitas Negeri Malang, 2023)
This study aims to reveal: 1) Describe and analyze the concept of Adab education according to Syed Muhammad Naquib Al-Attas, 2) Describe and analyze the implementation of Adab in education according to Syed Muhammad Naquib al-Attas. This research uses a qualitative approach, the nature of library research, and the type of research is document/text studies data collection techniques using document analysis. The data analysis technique used is content analysis. The survey results show that: 1) The concept of adab education, according to Syed Muhammad Naquib Al-Attas, uses the term Ta'dib which has a comprehensive meaning when compared to terms often used in Islamic education, such as tarbiyah and ta'lim. Ta'dib, according to Al-Attas, is giving manners and educating. Educating is an effort to instill and teach adab in humans in education. Through the term ta'dib, it is hoped that the knowledge gained can lead humans to become more civilized. 2) The implementation of adab in education, according to Syed Muhammad Naquib al-Attas, is: a) Recognizing one's self consists of 2 elements, namely reason and animalistic nature; b) Applying/comply with social norms; c) Applying discipline; d) Utilize and put something in its place; e) Recognizing and acknowledging the right and proper place to communicate, and f) bringing adab into the spiritual realm.